The clinical significance of carbapenem-resistant Klebsiella pneumoniae rectal colonization in critically ill patients: from colonization to bloodstream infection - Kontopoulou, Konstantina; Iosifidis, Elias; Antoniadou, Eleni; Tasioudis, Polychronis; Petinaki, Efthymia; Malli, Ergina; Metallidis, Symeon; Vatopoulos, Alkiviadis; Malisiovas, Nicolaos (Journal of Medical Microbiology, 2019)
Purpose . To highlight the clinical significance of carbapenem-resistant Klebsiella pneumoniae (CRKP) rectal colonization by examining the risk factors for CRKP rectal colonization and subsequent bloodstream infection (BSI) in critically ill patients. Methodology . Prospective study of CRKP rectal colonization in an intensive care unit (ICU) during a 39-month period. CRKP strains isolated from both the blood cultures and corresponding rectal specimens (n=96) of patients were screened by PCR for the presence of antibiotic resistance-associated genes. Molecular analyses were conducted to investigate the clonal relatedness of CRKP strains from the rectal and blood specimens. Results . Among the 498 patients, 226 were rectally colonized by CRKP, 48 of whom developed a CRKP BSI. The median time from hospital admission to the detection of CRKP rectal colonization was 8 days, while the median time from colonization to BSI was 4 days. The duration of ICU stay, patient/nurse ratio and prior use of antianaerobic antimicrobials were associated with CRKP rectal colonization. No specific factor was associated with BSIs in the colonized patients. The bla KPC-2 gene was detected in all 96 strains, which were all classified as sequence type ST-258. Representative pairs (n=48) of CRKP strains colonizing and infecting the same patient shared the same pulsotype. Conclusion . Our results indicate that hospitalized patients become infected with their colonizing strains, supporting the strong association between colonization and BSI. Limiting antianaerobic antimicrobial administration, reducing the duration of ICU stay and maintaining a low patient/nurse ratio are possible strategies to restrict rectal CRKP colonization in ICUs.
Keywords: bloodstream infections